Pengenalan Canva Sebagai Media Desain Grafis Untuk Meningkatkan Kreativitas - nurulhidayah; Diana Nur Septiana; Moch. Imam Soebachtiar; Ma'ruf Muzakki (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
Creative thinking skills are essential 21st-century competencies that must be developed early. In this digital era, technological tools like Canva can serve as a medium to foster students' visual creativity at the elementary level. This activity was conducted through training and mentoring for 5th-grade students at SDN Panjunan 2. The material covered the basics of graphic design, the use of Canva features, and practical exercises to create visual works such as greeting cards and thematic posters. Students showed increased enthusiasm and ability to express ideas visually. Some of their works were displayed in a classroom gallery. Canva is proven to be an effective tool to promote students' creativity and can be an alternative creative learning medium based on digital technology.